Analisis Resepsi Anggota Yayasan POTADS Mengenai Anak Down Syndrome dalam Film The Peanut Butter Falcon - Siti Lintang Pertiwi; Kartika Suci Lestari Parhusip (UNIVERSITAS KALBIS, 2022)
Down syndrome is not a disease, but is a genetic disorder that can occur in men and women. This film tells Zak a child with Down syndrome who aspires to become a professional wrestler and Zak managed to defeat his opponent in the wrestling ring making everyone who sees become very impressed. This study aims to determine the meaning of members of the POTADS foundation regarding children with Down syndrome in the film The Peanut Butter Falcon. This study uses Stuart Hall's encoding-decoding theory with three positions namely dominant hegemony, negotiation, opposition. This study uses a constructivism paradigm with a qualitative approach and descriptive research type. The author analyzes this research using the reception analysis method. The results showed that there were differences in meaning in every informant about children with Down syndrome in the film The Peanut Butter Falcon. The dominant hegemony position is dominated by the meaning of informants about children with Down syndrome interacting with strangers and in the position of opposition is dominated by the meaning of informants about children with Down syndrome who make a plan.